Impact of hyperuricemia on coronary blood flow and in-hospital mortality in patients with acute myocardial infarction undergoing percutaneous coronary intervention. Issue 3 (September 2022) - Nakahashi, Takuya; Sakata, Kenji; Masuda, Jun; Kumagai, Naoto; Higuma, Takumi; Ogimoto, Akiyoshi; Tanigawa, Takashi; Hanada, Hiroyuki; Nakamura, Mashio; Takamura, Masayuki; Dohi, Kaoru
Abstract: Background: Although serum uric acid (UA) is considered as a risk factor for cardiovascular disease, few data exist regarding the relationship between hyperuricemia, coronary blood flow, and subsequent outcome in patients with acute myocardial infarction (AMI). The purpose of our study is to assess whether hyperuricemia is associated with suboptimal coronary flow and increased risk of mortality in patients with AMI after percutaneous coronary intervention (PCI). Methods: Using the Rural AMI registry data, 989 consecutive patients with AMI who underwent emergent PCI and had UA measurement at admission were analyzed. We defined hyperuricemia as serum UA ≥7.0 mg/dL in men and ≥ 6.0 mg/dL in women. The primary endpoint was suboptimal coronary flow, defined as post PCI Thrombosis In Myocardial Infarction flow grade ≤ 2. The secondary outcome was in-hospital mortality. Results: Hyperuricemia was found in 249 (25.2%) patients. Patients with hyperuricemia were more often complicated with cardiogenic shock compared with those without (16.9% vs. 7.4%, p < 0.001). In addition, the median high-sensitivity C-reactive protein was significantly higher in patients with hyperuricemia (0.18 mg/dL; IQR, 0.09–0.71 mg/dL) than in those without (0.14 mg/dL; IQR, 0.07–0.41 mg/dL, p < 0.05). Under these conditions, the prevalence of suboptimal coronary flow after PCI (17.3% vs. 10.1%, p < 0.05) and in-hospital mortality (10.8% vs. 3.6%, p < 0.001) were significantly higher in patients with hyperuricemia compared with those without. Multivariable logistic regression analysis revealed that hyperuricemia was significantly associated with suboptimal coronary flow [odds ratio (OR), 1.60; 95% confidence interval (CI), 1.02–2.49; p < 0.05] and in-hospital mortality (OR, 2.08; 95% CI, 1.05–4.12; p < 0.05). Conclusions: Assessment of serum UA upon admission provides useful information for predicting suboptimal coronary flow and in-hospital mortality in patients with AMI undergoing PCI. Graphical abstract: Unlabelled Image Highlights: Hyperuricemia was found in one-fourth of all patients with acute myocardial infarction (AMI). Hyperuricemia was associated with suboptimal coronary flow in patients with AMI. Patients with hyperuricemia and suboptimal coronary flow had highest mortality.